2015
DOI: 10.1245/s10434-015-4908-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oncological Safety of Fat Grafting After Breast-Conserving Therapy: A Prospective Study

Abstract: The recurrence rate in patients reconstructed with fat grafts after BCT was not significantly different from the recurrence rate of control BCT patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…Additional meta-analysis of the remaining unmatched cohorts 26,40,42,44,47,49,61,68,71 was possible only for the IRD of LRR for period C, as control subjects did not have a disease-free interval (period A) equivalent to that in the AFT group. The overall IRD was -0⋅27 (-0⋅43 to -0⋅11) per cent per year, with a significantly lower overall LRR rate among patients who had AFT (P = 0⋅004).…”
Section: Results Of Meta-analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Additional meta-analysis of the remaining unmatched cohorts 26,40,42,44,47,49,61,68,71 was possible only for the IRD of LRR for period C, as control subjects did not have a disease-free interval (period A) equivalent to that in the AFT group. The overall IRD was -0⋅27 (-0⋅43 to -0⋅11) per cent per year, with a significantly lower overall LRR rate among patients who had AFT (P = 0⋅004).…”
Section: Results Of Meta-analysismentioning
confidence: 99%
“…Finally, data from all non-overlapping populations in case series 17 -19,21,24,27,28,30,33,35,36,38,43,46,50,52-54,56,63,64,67,72,74 as well as AFT treatment arms of cohort studies (References 26,31,32,[39][40][41][42]45,47,49,61,68,70,71 and T. Krastev et al,unpublished results) were pooled to provide an estimate of the combined incidence rate of LRR after exposure to AFT (period B). The raw incidence rate for all patients was 0⋅73 (0⋅56 to 0⋅94) per cent per year ( Fig.…”
Section: Results Of Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, using a model of autologous fat grafting, Massa et al reported increased proliferation of several breast cancer lines co-cultured with either induced adipocytes (i.e., differentiated from fibroblasts) or intact adipose tissue samples obtained from liposuction patients (245). However, a recently published prospective matched case-control analysis found no significant differences in locoregional recurrence in patients who received autologous fat grafting versus those who did not (249). Although cases and controls were matched for hormone receptor status in this study, no analysis was conducted to evaluate potential differences in recurrence by molecular tumor subtype, potentially due to the limited sample size and low locoregional event rate.…”
Section: Microenvironmental Links Between Adipose Tissue and Cancermentioning
confidence: 99%